Intervention in autism based on Early Start Denver Model in a multiethnic immigrant setting-experiences of preschool staff involved in its implementation - Petra Linnsand; Petra Linnsand; Gudrun Nygren; Gudrun Nygren; Jonas Hermansson; Christopher Gillberg; Emilia Carlsson; Emilia Carlsson (Frontiers Media S.A., 2024)
BackgroundEarly interventions for young children with autism have been shown to enhance developmental outcomes. However, opportunities for targeted interventions in autism, both in care and preschool, are often lacking, particularly in immigrant communities. The early start denver model (ESDM) stands as one of the most well-established intervention models, including improvement in core developmental domains and reduction of maladaptive behaviours, also delivered in preschool settings. An intervention program based on the ESDM was implemented in collaboration with parents, preschool staff, and health care professionals locally in a multiethnic immigrant and socioeconomically disadvantaged area in Gothenburg, Sweden.PurposeThe present study aimed to describe a low intensity intervention program based on the ESDM for young children with autism in a multiethnic immigrant setting and capture the experiences of the preschool staff involved in implementing the program.MethodFifteen preschool professionals were interviewed through focus group interviews. Data were analyzed using content analysis. The interviews focused on capturing the crucial factors in the intervention program and to get more in-depth information about the intervention program's influence on the children with autism, their parents, the preschool staff, and preschool activities.ResultsCentral components of the intervention program were emphasized by the preschool staff. These encompassed contextual prerequisites, such as the preschool staff's participation in intervention program fostered by the local environment and features linked to the ESDM methodology. The preschool staff emphasized that shared objectives and regular network meetings as fundamental components of the model. They also underscored the seamless alignment between the ESDM and the preschool curriculum emphasizing how ESDM strategies could be easily integrated into the preschool's daily routines. The staff's experience indicated that the implementation of ESDM enriched the learning experiences of children with autism and yielded benefits to their parents, fellow peers in the preschool, and the preschool staff.ConclusionsThe intervention program based on the ESDM presents a promising model for young children with autism in a multiethnic immigrant setting. Several critical factors based on the preschool staff's experiences were essential for implementation: contextual prerequisites such as organizational support, close collaboration with healthcare professionals, good competence among preschool staff, and the ESDM itself.